The Effect of Net Profit Margin and Total Asset Turn Over on Return on Investment at Transmart Indonesia Employee Cooperative Period 2012–2021 - Indriani, Dian; Sari, Widya Intan (Doktoral Ilmu Manajemen, Universitas Pasundan, 2023)
This research aims to determine the effect of Net Profit Margin and Total Asset Turn Over on Return On Investment in the Transmart Indonesia Employee Cooperative, either partially or simultaneously. The research method used in this research is quantitative descriptive research and uses statistical analysis. The population used is the financial report of the Transmart Indonesia Employee Cooperative. The sample used is data originating from notes on financial reports, balance sheets and profit and loss reports of the Indonesian Transmart Employee Cooperative for the period 2012 to 2021. The variables used in this research consist of the Net Profit Margin and Total Asset Turn Over variables , as the independent variable and the Return On Investment variable as the dependent variable. The research results obtained show that Net Profit Margin and Total Asset Turn Over have a significant effect on Return On Investment. The results of the simultaneous test (F test) show that the independent variables (Net Profit Margin and Total Asset Turn Over) simultaneously have a significant effect on the Return On Investment variable.